Apex hydrogen bonds in dendron assemblies modulate close-packed mesocrystal structures. Issue 45 (8th November 2022) - Jun, Taesuk; Park, Hyunjun; Jeon, Seungbae; Ahn, Hyungju; Jang, Woo-Dong; Lee, Byeongdu; Ryu, Du Yeol
Abstract : Dendron assemblies consisting of G2-CONH2 and G2-CH2 NH2 show the core-interaction-dependent mesocrystal structures of A15–σ–DDQC–C14. The more size-dispersed particles, the more susceptibility to chain exchange with increasing temperature. Abstract : The close-packed mesocrystal structures from soft-matter assemblies have recently received attention due to their structural similarity to atomic crystals, displaying various sphere-packing Frank–Kasper (FK) and quasicrystal structures. Herein, diverse mesocrystal structures are explored in second-generation dendrons (G2-X) designed with identical wedges, in which the terminal functionalities X = CONH2 and CH2 NH2 represent two levels of the strong and weak hydrogen-bonding apexes, respectively. The cohesive interactions at the core apex, referred to as the core interactions, are effectively modulated by forming heterogeneous hydrogen bonds between these two functional units. For the dendron assemblies compositionally close to each pure component of G2-CONH2 and G2-CH2 NH2, their own FK A15 and C14 phases dominate other phases, respectively. We show the existence of the wide-range FK σ including the dodecagonal quasicrystal (DDQC) phases from the dendron mixtures between G2-CONH2 and G2-CH2 NH2, providing an experimental phase sequence of A15–σ–DDQC–C14 as the core interactions are alleviated. Intriguingly, the temperature dependence of particle sizes shows that the high plateau values of particle sizes are maintained equivalently until each threshold temperature ( T th ), followed by a prompt decrease above the T th . A decrease in T th by alleviating the core interactions and its composition dependence suggest that the more size-dispersed particles, the more susceptibility to chain exchange with increasing temperature. Our results on the formation of supramolecular dendron assemblies provide a guide to understand the core-interaction-dependent mesocrystal structures toward the fundamental principle underlying the temperature dependence of their particle sizes.